2017
DOI: 10.5114/fmpcr.2017.65088
|View full text |Cite
|
Sign up to set email alerts
|

Impact of demographic factors on usage of stress coping strategies chosen by elderly people

Abstract: Background. Old age is a particular time in which people experience plenty of changes -both progressive and regressive. Their social and economic position is changing, and human beings are confronted with a lot of difficult situations, such as the death of a spouse, illness, retirement -which particularly require them to apply a proper strategy of coping with stress. Objectives. The aim of this study was to analyze the relationship between the demographic factors and strategies of coping with stress used by el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…Previous findings also confirmed that pandemic changes emotion recognition in a confinement situation (Meléndez, Satorres, Reyes‐Olmedo, Delhom, Real & Lora , 2020 ). Although the consequences of the restrictive lockdown and protracted pandemic affect both women and men, based on previous research, we suppose to observe some gender differences in the level of stress experienced, its evaluation, and the stress‐coping intensity (Asturias, Andrew, Boardman & Kerr, 2021 ; Ishiguro, Inoue, Fisher et al ., 2019 ; Lembas, Starkowska, Mak et al ., 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous findings also confirmed that pandemic changes emotion recognition in a confinement situation (Meléndez, Satorres, Reyes‐Olmedo, Delhom, Real & Lora , 2020 ). Although the consequences of the restrictive lockdown and protracted pandemic affect both women and men, based on previous research, we suppose to observe some gender differences in the level of stress experienced, its evaluation, and the stress‐coping intensity (Asturias, Andrew, Boardman & Kerr, 2021 ; Ishiguro, Inoue, Fisher et al ., 2019 ; Lembas, Starkowska, Mak et al ., 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…individual factors are emphasized as stressful factors at work by others as well [4]. another study has revealed that younger age and female gender are significant predictors of a greater stress score [21][22][23]. What is more, lack of knowledge was seen as a factor influencing stress in yet a further study [26].…”
Section: Resultsmentioning
confidence: 99%
“…Stress expression is influenced by various psychosocial and demographic factors. Herein, education, age, and gender have a different correlation with the distress expression [21,22]. psychosocial factors have a direct effect on stress by changing posture through stress.…”
mentioning
confidence: 99%
“…Moreover, people with higher levels of education turn to religion less often, whereas individuals with lower levels of education use positive reframing less often. Therefore, people with lower levels of education are perceived to be less capable of coping quickly with stressful situations than those with higher levels of education (Lembas et al, 2017 ; Nielsen et al, 2008 ).…”
Section: Theoretical Backgroundmentioning
confidence: 99%